Oleozon in the treatment of chronic edematous and fibroedematous gingivitis (Ozone Therapy Global Journal, 2021)
Introduction: Chronic gingivitis is defined as an immuno-inflammatory process that affects the protective periodontium.Objective: The effectiveness of Oleozon® in the edematous and fibroedematous gingivitis was evaluated.Material and methods: A quasi-experimental study of therapeutic intervention was carried out during the period from January 2017 to July 2019, a non-probabilistic sampling by criteria was used, 132 patients were included in the sample, who underwent a clinical history, oral examination, dental plaque controls and control of risk factors prior to the application of Oleozon®, the treatment was applied once a week for 6 sessions; The gingival index was used to evaluate the severity of gingivitis and the O'Leary index to evaluate oral hygiene.Results: Male patients between the ages of 40-55 years old and poor oral hygiene predominated; the severity of gingivitis increased as oral hygiene became more unfavorable. Before treatment, most of the periodontal segments were affected by bleeding, calculus and periodontal pockets and, at the end of treatment these decreased significantly, both in edematous and fibroedematous gingivitis, the clinical characteristics of the gingiva were recovered, the severity of the gingiva decreased as well as the pocket depth, texture and contour were restored, and bleeding decreased.Conclusions: Oleozon® is considered an effective drug for the treatment of edematous and fibroedematous gingivitis.